2015
DOI: 10.1097/nne.0000000000000129
|View full text |Cite
|
Sign up to set email alerts
|

Baby Boy Jones Interactive Case-Based Learning Activity

Abstract: Faced with limited resources, nurse educators are challenged with transforming nursing education while preparing enough qualified nurses to meet future demand; therefore, innovative approaches to teaching are needed. In this article, we describe the development of an innovative teaching activity. Baby Boy Jones is a Web-delivered, case-based learning activity focused on neonatal infection. It was created using e-learning authoring software and delivered through a learning management system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 1 publication
0
5
0
2
Order By: Relevance
“…A strong evidence base demonstrates distinct advantages of e‐learning as a new way of acquiring skills and knowledge in many areas, including nursing diagnoses. Different approaches have indicated that e‐learning is superior to traditional learning in stimulating critical and reflective analysis and learning (Cleveland, Carmona, Paper, Solis, & Taylor, ; Guhde, ), promoting transferability and learner‐centered approach (Cleveland et al., ; Irwin & Coutts, ), and providing knowledge and skill gains (Boada et al., ; Freire, Paula, Duarte, & Bueno, ; George et al., ; Lopes et al., ; McCutcheon, Lohan, Traynor, & Martin, ; Pobocik, ), student engagement (Irwin & Coutts, ; McCutcheon et al., ), and satisfaction (Gerdprasert, Pruksacheva, Panijpan, & Ruenwongsa, ; Jeffries, ; Kaveevivitchai et al., ; Kim, Chang, Lee, Jun, & Kim, ; McMullan, Jones, & Lea, ; Pourghaznein, Sabeghi, & Shariatinejad, ).…”
Section: Introductionmentioning
confidence: 99%
“…A strong evidence base demonstrates distinct advantages of e‐learning as a new way of acquiring skills and knowledge in many areas, including nursing diagnoses. Different approaches have indicated that e‐learning is superior to traditional learning in stimulating critical and reflective analysis and learning (Cleveland, Carmona, Paper, Solis, & Taylor, ; Guhde, ), promoting transferability and learner‐centered approach (Cleveland et al., ; Irwin & Coutts, ), and providing knowledge and skill gains (Boada et al., ; Freire, Paula, Duarte, & Bueno, ; George et al., ; Lopes et al., ; McCutcheon, Lohan, Traynor, & Martin, ; Pobocik, ), student engagement (Irwin & Coutts, ; McCutcheon et al., ), and satisfaction (Gerdprasert, Pruksacheva, Panijpan, & Ruenwongsa, ; Jeffries, ; Kaveevivitchai et al., ; Kim, Chang, Lee, Jun, & Kim, ; McMullan, Jones, & Lea, ; Pourghaznein, Sabeghi, & Shariatinejad, ).…”
Section: Introductionmentioning
confidence: 99%
“…In an undergraduate nursing study on the effectiveness of case-based learning using SoftChalk, Cleveland et al found a significant difference in the pre-and post-activity assessments (paired t-test p<0.001, n=315) (32). A study on dental students using SoftChalks for reviews at the beginning of a course instead of lectures found that review modules significantly increased post-test outcomes by 46%…”
Section: How Online Learning Is Uniquementioning
confidence: 99%
“…This is not to say educators should tell students this is all you need to know but rather guide student learning in explicitly stating crucial points (12,32,44,47).…”
Section: Student Perceptions Of Online Learning Modulesmentioning
confidence: 99%
See 2 more Smart Citations